Ancient marine reptiles - Callaway, Jack M.; Nicholls, Elizabeth L., 1946- (Academic Press, 1997)
Vertebrate evolution has led to the convergent appearance of many groups of originally terrestrial animals that now live in the sea. Among these groups are familiar mammals like whales, dolphins, and seals. There are also reptilian lineages (like plesiosaurs, ichthyosaurs, mosasaurs, thalattosaurs, and others) that have become sea creatures. Most of these marine reptiles, often wrongly called "dinosaurs", are extinct. This edited book is devoted to these extinct groups of marine reptiles. These reptilian analogs represent useful models of the myriad adaptations that permit tetrapods to live in the ocean. Key Features * First book in more than 80 years devoted exclusively to fossil marine reptiles * Documents the most current research on extinct marine reptiles * Prepared by the world's most prominent experts in the field * Well illustrated.